"The Impact of International Public Sector Accounting Standards (IPSASs) on the Public Budget in Iraq" - محمد, صفاء احمد; كامل, رؤى مصطفى (Journal of Economics and Administrative Sciences, 2018)
The aim of the research is to determine the impact of the Iraqi public budget on IPSASs by conducting the questionnaire; the research was based on the hypothesis that "there is an impact of the adoption of the International Accounting Standards in the general budget of Iraq”. The research concluded that the government accounting system closely interferes with the general budget at all stages. The shifting towards the accrual basis is the first element of the reform package towards reaching the reform of the state budget. Without reforming government accounting, it is almost impossible to develop the budget. IPSASs are a recognized reference to the assessment and development of government accounting in developing countries. The adoption of IPSASs on an accrual basis helps to provide useful information that helps to strengthen the planning process for subsequent years' budget and enhance financial performance control. The study recommended the need for the concerned parties to amend some of the legislation and laws for the general budget and for all stages to provide a basic basis for the shifting towards the adoption of the basis of accrual, it is  also recommended adapting the Iraqi government accounting system and the current financial and accounting manual with IPSASs requirements and in line with the requirements of the economic and political environment in Iraq, which requires shifting towards adopting the budget of programs and performance instead of the current traditional budget, and that the planning of the general budget in the medium term to provide an opportunity for compatibility with the accrual basis.